Analysis of Investment Education and Understanding of Gold Derivative Products at PT RFB - Rizka Brillianti Wisnu Anggraini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The development of investment activity in Indonesia has shown rapid growth, particularly in derivative instruments such as gold derivatives, which offer profit opportunities through fluctuations in the price of gold on the global market. However, these potential profits are accompanied by a relatively high level of risk, so investors need a sufficient understanding of the market before investing. This study aims to examine the implementation process of investment education related to Gold Derivative products conducted by PT RFB, analyze the role of such education in helping investors understand investment risks and opportunities, and identify the challenges faced in its implementation. This study employs a qualitative approach using a descriptive method, with data collected through observation and interviews with company representatives. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of this study are expected to provide an overview of the implementation of investment education conducted by futures brokerage firms in enhancing investors' understanding of Gold Derivative products, while also contributing to improving public financial literacy and supporting more rational and well-planned investment decision-making